Explore Drones - Starr, Abbe L.; Kaiser, Brianna (Minneapolis : Lerner Publications, 2024)
"Drones are commonly used by the military, scientists, and more. Discover the beginning of drones, how and why people use drones today, and where the future of drones could be headed"-- Provided by publisher
t t
Includes index
Keywords: Drone aircraft -- Juvenile literature; Juvenile literature